Hard headed woman [compact disc] - Price, Margo, 1983- (Loma Vista Recordings, 2025)
For nearly a decade, Margo Price has created a lane where independent-minded, insurgent country music can exist and thrive alongside the mainstream. Now she's back with an exquisite, timeless album that reconnects with her roots.